Posterior Reversible Encephalopathy Syndrome After Self-Medication With an Oral Decongestant: A Case Report - Zerbib, Yoann; Gibert, Louis; Bennis, Youssef; Masmoudi, Kamel; Maizel, Julien; Brault, Clément (Frontiers in Medicine, 2022)
Introduction: Posterior Reversible Encephalopathy Syndrome (PRES) is a rare neurological disorder related to a dysregulation of cerebral perfusion Case presentation: We report the case of a 18-year-old female patient with a medical history of end-stage renal disease, given hemodialysis 3 times a week, admitted to the emergency department with mental confusion, blurred vision, headaches and vomiting, after self-medication of oral decongestant. Explorations showed hypointense lesions on the T1-weighted Magnetic Resonance Images (MRI) and hyperintense areas on the T2-weighted and fluid-attenuated inversion recovery (FLAIR) MR sequences, with lack of diffusion restriction consistent with PRES. Concomitant Enterobacter cloacae hemodialysis catheter-bloodstream infection was diagnose. We speculate that both sepsis and inappropriate self-medication with oral decongestant have contributed to hypertension, endothelial dysfunction and vasogenic edema. Recovery was complete after ICU management. Discussion: PRES is life-threatening condition that requires ICU admission. Etiology identification and treatment is the keystone of medical care. Inappropriate self-medication with oral decongestant may trigger PRES, highlighting the important role of patient’s education.